"Being Mindful": Does it Help Adolescents and Young Adults Who Have Completed Cancer Treatment?. (July 2015) - Patterson, Pandora; McDonald, Fiona E. J.
Purpose: Feelings of excitement and relief upon finishing cancer treatment are often juxtaposed with a time that can be challenging, distressing, and uncertain for adolescents and young adults (AYAs). The purpose of this study was to examine whether a mindful dispositional trait was associated with better adaptive outcomes for these young people.Methods: AYAs who had finished cancer treatment (N = 76; mean age, 18.5; years, SD, 3.4 years) completed questionnaires measuring mindfulness, psychological distress, and uncertainty around their cancer experience. A median split was performed based on the total scores for the mindfulness measure to establish high and low mindfulness groups.Results: No significant differences were found between these 2 groups on demographic or cancer variables. There were significant differences between the groups on the distress and uncertainty scores such that the higher mindfulness group reported significantly less distress and uncertainty.Conclusions: The current findings suggest the potential for a broader application of mindfulness to more fully assist young people throughout the whole pathway of cancer care.